Screens From Materiality to Spectatorship - A Historical and Theoretical Reassessment - Chateau, Dominique; Moure, José (The Key Debates: Mutations and Appropriations in European Film Studies, 2016)
We live in an era of screens. No longer just the place where we view movies, or watch TV at night, screens are now ubiquitous, the source of the majority of information we consume daily, and a crucial component of our basic interactions with colleagues, friends, and family. This transformation has happened almost without us realizing it-and certainly without the full theoretical and intellectual analysis it deserves. Screens brings together scholars from a variety of disciplines to analyse the growing presence and place of screens in our lives today. They tackle such topics as the archaeology of screens, film and media theories about our interactions with them, their use in contemporary art, and the new avenues they open up for showing films and other media in non-traditional venues.